Respuesta :

Answer:

(d) They may be combines

Step-by-step explanation:

Given

[tex]6\sqrt{32} - 12\sqrt{72}[/tex]

Required

Which option is true

Express 32 as 16 * 2 and 72 as 36 * 2

[tex]6\sqrt{32} - 12\sqrt{72} = 6\sqrt{16 * 2} - 12\sqrt{36 * 2}[/tex]

Split

[tex]6\sqrt{32} - 12\sqrt{72} = 6\sqrt{16} * \sqrt{2} - 12\sqrt{36} * \sqrt{2}[/tex]

This gives:

[tex]6\sqrt{32} - 12\sqrt{72} = 6*4 * \sqrt{2} - 12*6 * \sqrt{2}[/tex]

[tex]6\sqrt{32} - 12\sqrt{72} = 24 * \sqrt{2} - 72 * \sqrt{2}[/tex]

[tex]6\sqrt{32} - 12\sqrt{72} = 24 \sqrt{2} - 72 \sqrt{2}[/tex]

Since both term have the same radicand, then:

[tex]6\sqrt{32} - 12\sqrt{72} =( 24 - 72 )\sqrt{2}[/tex]

[tex]6\sqrt{32} - 12\sqrt{72} =-48\sqrt{2}[/tex]

Option (d) is correct

ACCESS MORE